Determination of Hartebeesthoek Radio Astronomy Observatory (HartRAO) VLBI antenna parameters and local tie for improved global reference frames - Combrinck, Ludwig (University of Pretoria, 2023)
Thesis (PhD (Geoinformatics))--University of Pretoria, 2022.